2022
DOI: 10.1038/s41598-022-27179-7
|View full text |Cite
|
Sign up to set email alerts
|

On the role of tail in stability and energetic cost of bird flapping flight

Abstract: Migratory birds travel over impressively long distances. Consequently, they have to adopt flight regimes being both efficient—in order to spare their metabolic resources—and robust to perturbations. This paper investigates the relationship between both aspects, i.e., energetic performance and stability, in flapping flight of migratory birds. Relying on a poly-articulated wing morphing model and a tail-like surface, several families of steady flight regime have been identified and analysed. These families diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…higher) velocities, which is consistent with the observations of [ 23 ], who observed that birds tend to furl their tails in fast flight. Finally, it is shown in [ 24 ] that the cost of transport of large flapping birds increases with the opening angle of their tails, and that reducing tail lift thus improves flight efficiency. Since our scenario concerns steady flapping flight at a high forward velocity, for a large bird with a high aspect ratio, we consider that the assumption of low tail lift is reasonable.…”
Section: Methodsmentioning
confidence: 99%
“…higher) velocities, which is consistent with the observations of [ 23 ], who observed that birds tend to furl their tails in fast flight. Finally, it is shown in [ 24 ] that the cost of transport of large flapping birds increases with the opening angle of their tails, and that reducing tail lift thus improves flight efficiency. Since our scenario concerns steady flapping flight at a high forward velocity, for a large bird with a high aspect ratio, we consider that the assumption of low tail lift is reasonable.…”
Section: Methodsmentioning
confidence: 99%
“…Modeling wing pitch independent of body pitch has plausible biological footing, as the wing pitch is presumed to emanate from the rotation of the humerus at the shoulder joint. Adding this degree of freedom at the shoulder is a departure from common avian flight dynamics modeling frameworks premised on a wing with its root fixed to the body [42,49,50]. However, the latter frameworks are typically applied to rhythmic flapping and steady-state gliding conditions where the dynamics of the wing root may not significantly impact averaged or longer time-scale dynamics.…”
Section: Bio-inspired Modeling Frameworkmentioning
confidence: 99%
“…Harvey et al elucidates how control over the elbow and wrist joints in concert with the aerodynamic and inertial properties allows birds to actively transition between regimes of static and dynamic stability [4,37,41]. Ducci et al identifies how passively stable flight regimes can be accessed in steady flapping flight with a high-fidelity multi-body model featuring both tail and wing morphing [42]. Strong precedent for the current investigation may be found in chapter 8 of Ducci's dissertation [43], where the author obtains preliminary results indicative of enhanced flapping flight stability by modeling the effect of the powerful pectoralis and supracoracoideus muscles acting on the shoulder as a viscoelastic driven element.…”
Section: Introductionmentioning
confidence: 99%